Hobbit : The desolation of Smaug - Jackson, Peter, 1961-; Walsh, Fran, 1959-; Boyens, Philippa; Toro, Guillermo del, 1964-; Cunningham, Carolynne; Weiner, Zane; Horn, Alan (Alan F.); Emmerich, Toby; Kamins, Ken; Blackwood, Carolyn; Lesnie, Andrew, 1956-2015; Olssen, Jabez; et al. (Burbank, California Distributed by Warner Home Video, 2014)
Bilbo Baggins continues on in his journey with the wizard Gandalf and thirteen dwarves, led by Thorin Oakenshield, on an epic quest to reclaim their lost Dwarf Kingdom of Erebor.--
Disc 1. [The movie] -- Disc 2. Special features
Based on the novel by J.R.R. Tolkien.
Originally released as a motion picture in 2013.
Special features: Disc 1. "New Zealand, home of Middle Earth, part 2." Disc 2. "In the company of the Hobbit" making of featurette; "All in a day's work" making of featurette; "I see fire" music video; Live event: in the cutting room; Production videos; Trailers.
Director of photography, Andrew Lesnie ; production designer, Dan Hennah ; edited by Jabez Olssen ; costume designers, Bob Buck, Ann Maskrey, Richard Taylor ; music composed by Howard Shore ; armour, weapons, creatures and special makeup, Richard Taylor ; visual effects supervisor, Eric Saindon ; animation supervisors, David Clayton, Eric Reynolds ; "I see fire" performed by Ed Sheeran ; executive producers, Alan Horn, Toby Emmerich ; executive producers, Ken Kamins, Carolyn Blackwood.
Ian McKellen, Martin Freeman, Richard Armitage, Benedict Cumberbatch, Evangeline Lilly, Lee Pace, Luke Evans, Stephen Fry, Ken Stott, James Nesbitt, Orlando Bloom, Mikael Persbrandt, Sylvester McCoy, Aidan Turner, Dean O'Gorman, Graham McTavish, Adam Brown, Peter Hambleton, John Callen, Mark Hadlow, Jed Brophy, William Kircher, Stephen Hunter, Ryan Gage, John Bell, Manu Bennett, Lawrence Makoare.
MPAA rating: PG-13; extended sequences of intense fantasy action violence, and frightening images.
Keywords: Tolkien, J. R. R. -- 1892-1973 -- Film adaptations; Baggins, Bilbo -- Drama; Gandalf -- Drama; Middle Earth (Imaginary place) -- Drama; Hobbits (Fictitious characters) -- Drama; Treasure troves -- Drama; Wizards -- Drama; Dwarfs (Folklore) -- Drama; Dragons -- Drama; Video recordings for the hearing impaired; Film adaptations of books; Feature films -- United States; Feature films -- New Zealand; Video recordings for the hearing impaired; Fiction films; Feature films; Fantasy films; Action and adventure films; Drama; Film adaptations; Adventure films